Casteing Race: Enlightenment Encounters with the Brahmin. - Jain, Shruti (Eighteenth Century Fiction, 2025)
Taking Voltaire's engagement with India as a case study, this article argues that the hermeneutic of caste has a crucial role to play in the development of Enlightenment thought. Voltaire relies on the authority of the Brahmin figure, along with a deference to (forged) scriptures like the Ezourvedam, to construct a notion of caste antiquity that he then employs to articulate a systematic attack on biblical teleology. This a perfect example of complex pre-Orientalism produced by liberal Enlightenment thinkers in the eighteenth century. Indian caste power hierarchies work in collaboration with colonial hierarchies to maintain and generate the structures that serve the upper caste and classes across Europe and Asia. Furthermore, the ideas about caste produced in the eighteenth century played a role in codifying and homogenizing Hinduism.